Development of Physics Teaching Materials Based on Science Process Skills and Their Influence on Critical Thinking - Hidayatun Nisa; Helmi; Kaharuddin Arafah (Postgraduate, University of Mataram, 2026)
This study aims to analyze the content validity of the developed Science Process Skills (SPS)-based physics instructional materials; analyze the responses of educational practitioners regarding the quality and practicality of the materials; and analyze the effect of the developed SPS-based physics instructional materials. The research employed the Research and Development (R&D) method with the 4D model (Define, Design, Develop, and Disseminate). The developed product was validated by three experts, its practicality was assessed by ten physics teachers, and it was tested on 36 tenth-grade students. The instruments used in this study included a validation sheet for the instructional materials, a practitioner response questionnaire, and a validated critical thinking skills test for students. The results showed that the SPS-based physics instructional materials were validated using Aiken’s V index, with an average score of 0.81 for content feasibility, 0.82 for presentation, 0.82 for language, and 0.81 for graphical aspects. The overall average score was 0.82. The hypothesis testing showed that tcount = 8.006 ≥ ttable = 1.994, indicating a significant difference in critical thinking ability between students taught using the SPS-based physics materials and those taught using conventional materials. Based on these findings, the developed SPS-based physics instructional materials are valid according to experts, practical based on teachers’ assessments, positively received, and effective in improving students’ critical thinking skills, thus feasible for implementation in physics learning as a supportive medium to enhance students’ critical thinking abilities.